Sleeve gastrectomy attenuated diabetes-related cognitive decline in diabetic rats - Ding, Huanxin; Liu, Chuxuan; Zhang, Shuo; Li, Bingjun; Xu, Qian; Shi, Bowen; Li, Songhan; Dong, Shuohui; Ma, Xiaomin; Zhang, Yun; Zhong, Mingwei; Zhang, Guangyong (Frontiers in Endocrinology, 2022)
Objective: To investigate the effects of sleeve gastrectomy (SG) on diabetes-related cognitive decline (DCD) in rats with diabetic mellitus (DM). Methods and methods: Forty Wistar rats were randomly divided into control (CON) group (n=10), diabetes mellitus (DM) group (n=10), sham operation (SHAM) group (n=10) and SG group (n=10). DM model was established by high-fat diet (HFD) combined with intraperitoneal injection of streptozocin (STZ). Behavioral evaluation was given using Morris water maze test and Y-maze. In addition, PET-CT, TUNEL assay, histological analysis, transmission electron microscopy (TEM), immunohistochemistry (IHC) and Western blot analysis were used to evaluate the alleviating effects and potential mechanisms of SG on DCD in DM rats. Results: Compared with the sham group, SG induced significant improvement in the metabolic indices such as blood glucose and body weight. Besides, it could attenuate the insulin resistance compared with SHAM group. In addition, SG could improve the cognitive function of DM rats, which were featured by significant decrease in the escape latency (P<0.05), and significant increase in the time in target quadrant and platform crossings (P<0.05) compared with the SHAM group. SG induced significant elevation in the spontaneous alternation compared with SHAM group (P<0.05). Moreover, SG could improve the arrangement and biosynthesis of hippocampus neuron. Moreover, SG triggered the inhibition of apoptosis of hippocampus neurons, and Western blot analysis showed SG induced significant increase in the ratios of Bcl-2/Bax and Caspase3/cleaved Caspase 3. TEM demonstrated SG could significantly improve the microstructure of hippocampus neurons compared with the SHAM group. Western blot and IHC confirmed the significant decrease in the phosphorylation of tau at Ser404 and Ser396 sites in the SG group. Furthermore, SG activated the PI3K signaling pathway by elevating the phosphorylation of PI3K and Akt and GSK3β compared with the SHAM group. Conclusion: SG attenuated the DCD in DM rats, which may be related to the activation of PI3K signaling pathway.